The economics of poverty - Batchelder, Alan B. (New York : Wiley, 1971)
This volume summarises the character and extent of poverty, and analyses its causes in the American context. The author also describes the programmes which transfer money from the non-poor to the poor, and looks at the various social welfare programmes designed to alleviate poverty; he also gives choices in the American setting on how to reduce poverty effectively.
Includes bibliographical footnotes and index.
lje 18/10/2018
Loans
Keywords: Poverty; Poor; Poverty-United States